Microplasma Array Patterning of Reactive Oxygen and Nitrogen Species onto Polystyrene - Szili, Endre J.; Dedrick, James; Oh, Jun-Seok; Bradley, James W.; Boswell, Roderick W.; Charles, Christine; Short, Robert D.; Al-Bataineh, Sameer A. (Frontiers in Physics, 2017)
We investigate an approach for the patterning of reactive oxygen and nitrogen species (RONS) onto polystyrene using atmospheric-pressure microplasma arrays. The spectrally integrated and time-resolved optical emission from the array is characterised with respect to the applied voltage, applied-voltage frequency and pressure; and the array is used to achieve spatially resolved modification of polystyrene at three pressures: 500 Torr, 760 Torr and 1000 Torr. As determined by time-of-flight secondary ion mass spectrometry (ToF-SIMS), regions over which surface modification occurs are clearly restricted to areas that are exposed to individual microplasma cavities. Analysis of the negative-ion ToF-SIMS mass spectra from the centre of the modified microspots shows that the level of oxidation is dependent on the operating pressure, and closely correlated with the spatial distribution of the optical emission. The functional groups that are generated by the microplasma array on the polystyrene surface are shown to readily participate in an oxidative reaction in phosphate buffered saline solution (pH 7.4). Patterns of oxidised and chemically reactive functionalities could potentially be applied to the future development of biomaterial surfaces, where spatial control over biomolecule or cell function is needed.